Analisis laporan keuangan dalam menilai kinerja keuangan pada Marketing Office CitraLand Winangun Manado - Pandoh, Tesalonika; Morasa, Jenny; Maradesa, Djeini (Riset Akuntansi dan Portofolio Investasi, 2024)
Financial reports are very helpful and very important for companies to know how a company's financial performance is in the current year and previous years. This research aims to analyze financial performance using the profit and loss report at the CitraLand Winangun Manado Marketing Office from 2021-2023. The type of research that will be used in this research is descriptive with a quantitative approach using primary data sources and secondary data. The research results based on liquidity ratios are not good enough because in fulfilling its obligations the company experiences several obstacles on the side of the company's current liabilities and for trend analysis it is also not good enough because in fulfilling its obligations the company experiences several obstacles such as the income generated is not enough to cover existing expenses but to Trend analysis can be said to be good because in the following year it has increased and the activity ratio from the first to the third year has decreased but it is also quite good because the fixed asset turnover has increased every year, while the solvency ratio, profitability ratio and trend analysis can be said to be good every year. year because the decrease in profit only occurred in the first year and the following year there was an increase.